Perancangan Motif Batik Tulis Ikon Kabupaten Ngawi Sebagai Media Promosi Dalam Menunjang Industri Kreatif - Apriliani, Ika Mega; Budiardjo, Hardman; Karsam, Karsam (Jurnal Art Nouveau, 2016)
Batik is a legacy of Indonesia which have been recognized or established by UNESCO since October 2, 2009. Batik has a significance or meaning in each of its motives. The rapid lovers of batik making it grows each days, until each region competing to have a motif that contains the meaning according to the characteristics or in accordance with the characteristic of the area. Unfortunately Ngawi region still lacks of its batik’s motif. Even around the year 2009 until the year 2010, Ngawi begans to experience the crisis of batik’s enthusiasts. Lessening on batik also the interest to develop the regional characteristics. In fact, if viewed from the potential contained in Ngawi, it’s very supportive to improve or develop Ngawi’s batik. Therefore, this study aims to design the icon of Ngawi’s batik’s motif as a media campaign in support of the creative industries. The design of this motif is using the method of data collection with qualitative way, that is by interview, observation and study of the existing literature, which is very important to determine the concept of the design that will be designed. From the results of the data collection, the concept that emerged is “Modern”. “Modern” is the concept of a motif‘s design, designed in a contemporary style or the present time to develop an existing motif. The concept is used by most of the motif’s design, good design and the chosen color. There should be an effort to attract the attention of Ngawi’s residents, thus motif were designed and packaged in a modern way, different from another existing motif. One of them is to design a motif that contains the icons of Ngawi by combining colors characteristic of Ngawi, by hoping that this medium can be a medium that can redevelop Ngawi’s batik, and boost the spirit batik’s enthusiasts, for Ngawi’s batik and the potential that Ngawi has can be known by the public. Kata Kunci: Motif Batik, Tulis, ikon, kabupaten Ngawi, Media Promosi, Industri Kreatif, Modern.